Insulin receptor antibody‐iduronate 2‐sulfatase fusion protein: Pharmacokinetics, anti‐drug antibody, and safety pharmacology in Rhesus monkeys. Issue 11 (5th August 2014) - Boado, Ruben J.; Ka‐Wai Hui, Eric; Zhiqiang Lu, Jeff; Pardridge, William M.
ABSTRACT Mucopolysaccharidosis (MPS) Type II is caused by mutations in the gene encoding the lysosomal enzyme, iduronate 2‐sulfatase (IDS). The majority of MPSII cases affect the brain. However, enzyme replacement therapy with recombinant IDS does not treat the brain, because IDS is a large molecule drug that does not cross the blood‐brain barrier (BBB). To enable BBB penetration, IDS has been re‐engineered as an IgG‐IDS fusion protein, where the IgG domain is a monoclonal antibody (MAb) against the human insulin receptor (HIR). The HIRMAb crosses the BBB via receptor‐mediated transport on the endogenous BBB insulin receptor, and the HIRMAb domain of the fusion protein acts as a molecular Trojan horse to ferry the fused IDS into brain from blood. The present study reports on the first safety pharmacology and pharmacokinetics study of the HIRMAb‐IDS fusion protein. Juvenile male Rhesus monkeys were infused intravenously (IV) weekly for 26 weeks with 0, 3, 10, or 30 mg/kg of the HIRMAb‐IDS fusion protein. The plasma clearance of the fusion protein followed a linear pharmacokinetics profile, which was equivalent either with measurements of the plasma concentration of immunoreactive HIRMAb‐IDS fusion protein, or with assays of plasma IDS enzyme activity. Anti‐drug antibody (ADA) titers were monitored monthly, and the ADA response was primarily directed against the variable region of the HIRMAb domain of the fusion protein. No infusion related reactions or clinical signs of immune response were observed during the course of the study. A battery of safety pharmacology, clinical chemistry, and tissue histopathology showed no signs of adverse events, and demonstrate the safety profile of chronic treatment of primates with 3–30 mg/kg weekly IV infusion doses of the HIRMAb‐IDS fusion protein. Biotechnol. Bioeng. 2014;111: 2317–2325. © 2014 Wiley Periodicals, Inc.